Ontology of Green Value Networks - Avelino, Juscimara Gomes; Silva, Patrício de Alencar (iSys - Journal of Information Systems, 2020)
The main purpose of a Value Network model is to make the businesses configured from this modeling technique potentially sustainable. However, in this type of conceptual modeling, sustainability is not always treated in its three dimensions (economic, social and environmental). To cope with this issue, this work proposes an ontology to leverage Value Network Modeling with concepts of environmental sustainability. The ontology supports semi-automatic configuration of value network models to help business analysts deciding upon alternative value paths to provide products or services the value of which depend on environmental accreditations or certifications.